Pengaruh Media Pembelajaran Permainan Ular Tangga terhadap Motivasi Belajar Geografi - Juwita Rahmi; Lailatur Rahmi (Universitas Negeri Gorontalo, 2025)
Students’ learning motivation in geography tends to be low, which affects their engagement during the learning process. This condition indicates the need for innovative learning media to enhance students’ interest and participation. This study aims to analyze the effect of using snakes and ladders game-based learning media on students’ motivation in geography learning. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The sample consisted of two classes, namely the experimental and control classes, each comprising 32 students. Data were collected using a learning motivation questionnaire administered before and after the treatment, and analyzed using t-test and N-Gain analysis. The results showed a significant difference between the experimental and control classes (Sig. 0.05). The average N-Gain of the experimental class was in the moderate to high category, while the control class was in the low category. The use of snakes and ladders learning media is effective in improving students’ learning motivation in geography.